BESTIE ASI: Langkah Awal Peningkatan Cakupan ASI Eksklusif di Puskesmas Kota Timur - Ibrahim, Sri Andriani; Rahma, St -; mulyadi, jesica -; iman, dian pratiwi; Lahay, Sitty Fadhila Fitrianty; Nagaring, Sulaiman Putra; Anita, Astri - (Universitas Negeri Gorontalo, 2025)
Breast milk is the best source of nutrition for babies and is recommended by the WHO to be given exclusively for the first six months of life. However, the coverage of exclusive breastfeeding in Gorontalo is still low, including in the working area of the East City Health Centre. One of the causes is the lack of knowledge among mothers about the benefits, breastfeeding techniques, breast milk storage, and stress management during breastfeeding. This activity aims to increase the knowledge of pregnant women through education using video and PowerPoint media in the BESTIE ASI (Breast Care, Essential Nutrients, Storage, Technique, and Stress Managed ASI) programme. The activity methods include planning, preparation, implementation of counselling, and evaluation using pre-tests and post-tests. There were 15 pregnant women participating in the activity. The evaluation results showed an increase in the average knowledge score from 46.67 on the pre-test to 70.67 on the post-test. Video and PowerPoint media were effective in increasing knowledge because they were able to present the material in an interesting, interactive, and easy-to-understand manner. Thus, educational activities using audio-visual media have been proven to support the improvement of pregnant women's readiness for exclusive breastfeeding.Keywords: exclusive breastfeeding, pregnant women, health education, video, PowerPoint